THE REACTUALIZATION OF NATIONALISM AS A STATE DEFENSE STRATEGY IN THE PERSPECTIVE OF THE NUSANTARA INTERPRETATION OF AL-QUR’AN - Arif Rakman Hakim, Moh.; Ubaidillah, Ubaidillah (State Islamic University North Sumatra, 2021)
Abstract: This study is focused to explain the national issues in the potential for disintegration, and disorientation of the nation’s citizens through a study of interpretation with a starting point towards conceptual terms such as balad, syu‘ûbah, and ummah. This research used the maudhu‘i method with the structural semantic theory approach of Thosohiko Izutsu, and the text, context, contextual theory of Abdullah Saeed. This study aims to explain the values of nationalism in al-Qur’an through terms that are close to the meaning of the state, and nation such as balad, ummah, and syu‘ûbah. The result showed that the maintaining the security and welfare of the country is an important thing that have todo in order to build a peaceful, and prosperous nation’s civilization. Actualizing wasathiyah Islamic values, strengthening unity in diversity, and creating security, and prosperity for a nation is one of the concepts of defending the state to maintain the values of Indonesianalism which has a high level of diversity.Keywords: nationalism, state defense, Nusantara Qur’anic interpretation